AB0089 The Role of the Serotonin Receptor Sert in Bone Remodeling. (9th June 2015) - Chen, R.; Chabbi-Achengli, Y.; Marty, C.; Cohen-Solal, M.; de Vernejoul, M.-C.; Collet, C.
Abstract : Background: Inhibitors of the SERT (SSRIs), the specific serotonin transporter, are efficient to treat depression. A decrease in bone formation has been reported in SERT-/- mice but their effects in bone remodelling are unclear. We have demonstrated that the osteoclast precursor needed serotonin to differentiate while SSRI Paroxetine was responsible for a decreased osteoclast differentiation. Objectives: We here aimed to study the bone phenotype and bone remodelling of SERT-/- mice in 129/Sv background, known to display an appropriate serotonin metabolism unlike C57BL/6J mice. The second aim was to evaluate the capacity of differentiation of precursors of bone cells in the absence of SERT. Methods: Bone histomorphometry was performed in 6 week-, 16 week- and 8 month-old SERT-/- mice. E x vivo experiment analyses were conducted to assess the capacity of bone forming and resorbing cells from the bone marrow as well as the expression of differentiating factors. Results: Compared to WT mice, SERT-/- mice had a decreased bone formation as shown by a lower bone formation rate and lower level of P1NP at 6 weeks, 16 weeks and 8 months. At 6 weeks of age only, lower osteoclast number was counted at femur level and lower level of TRAP in SERT-/- mice as compared to WT mice, suggesting a diminished bone resorption in SERT-/-only in the postnatal period. Moreover, we found a decreased number of osteoclasts, osteoblasts and osteoprogenitors in SERT-/- primary cultures. These results were confirmed in primary cells derived from WT mice cultured in the presence of Paroxetine. Furthermore, SERT-/- osteoblasts had a lower expression of RANKL and a higher expression of OPG to WT osteoblasts. Also, a diminution of the ratio RANKL/OPG was observed in SERT-/-mice leading to a blunted osteoclast differentiation. Conclusions: Our results indicate that the SERT favors bone formation and resorption. The inhibition of SERT might therefore conduct to a low bone mass and promote the development of bone fragility. Disclosure of Interest: None declared